Educational Attainment and Women's Agency: Evidence from Developing Countries (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Educational attainment is widely recognized as one of the most powerful instruments for promoting women's empowerment and agency in developing countries. Education enhances women's knowledge, skills, confidence, economic opportunities, and capacity to participate in household and societal decision-making processes. Over the past two decades, significant improvements in female educational participation have been observed across developing nations; however, disparities continue to exist in terms of educational access, quality, and outcomes. This paper reviews theoretical perspectives and empirical evidence on the relationship between educational attainment and women's agency in developing countries. Drawing upon Women's Empowerment Theory, Human Capital Theory, and Social Cognitive Theory, the paper examines how education influences women's decision-making power, economic participation, social mobility, leadership, and autonomy. The review highlights that advanced levels of education are consistently associated with higher agency and empowerment outcomes. However, structural barriers such as poverty, cultural norms, gender discrimination, and institutional constraints continue to limit the translation of educational achievements into actual empowerment. The paper concludes that educational attainment remains a fundamental driver of women's agency and sustainable development in developing countries.